HOW DOES ISLAMIC ART CONTRIBUTE TO ENRICHING ARAB-EUROPEAN CULTURAL DIVERSITY? - Mebarek Fadhila; Mohamedi Riahi Rachida (International Journal of Innovative Technologies in Social Science, 2025)
Islamic art promotes understanding and cross-cultural exchange, which greatly enriches the cultural diversity of Arabs and Europeans. From the Middle Ages onward, its complex geometric patterns, calligraphy, and arabesques have impacted European art, architecture, and design, as evidenced by the Gothic and Renaissance eras. During the 12th-century Renaissance, Islamic scientific and philosophical texts were translated into Latin, which promoted intellectual exchanges and helped incorporate Islamic artistic ideas into European philosophy. Islamic art museums and exhibitions in Europe help to close cultural gaps and foster a sense of shared heritage. This artistic exchange promotes a greater understanding of diversity and commonality in modern multicultural societies by highlighting historical connections between Arab and European civilisations in addition to celebrating aesthetic beauty.